If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 6(12 + -5x) = 6 -3x + (12 * 6 + -5x * 6) = 6 -3x + (72 + -30x) = 6 Reorder the terms: 72 + -3x + -30x = 6 Combine like terms: -3x + -30x = -33x 72 + -33x = 6 Solving 72 + -33x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-72' to each side of the equation. 72 + -72 + -33x = 6 + -72 Combine like terms: 72 + -72 = 0 0 + -33x = 6 + -72 -33x = 6 + -72 Combine like terms: 6 + -72 = -66 -33x = -66 Divide each side by '-33'. x = 2 Simplifying x = 2
| -4(3+x)+4(x-6)=-4 | | k^2-6k-9=18 | | -4x+7x-7=3(x-6)-1 | | 22+3x=2(x+3) | | -2y=-24+10x | | 25-7=18 | | 6-2(4x+1)=5x-2(2x+7) | | -5.2=m-6.8 | | -(x+7)=36 | | 5y+50-8= | | 19.6+n=24.62 | | -20=f/2 | | 2t^2-30t+0=0 | | X/-9=-14 | | 17=-6-6x-1 | | -10x-2(12-5x)=-24 | | abs(3x-5)=abs(4x-2) | | 8-(x*x+7)=-35 | | .22(x+6)=.2x+5.3 | | x/3-9/4=x/6-1/2 | | 5v^2-17v=-6 | | 1/x=4/12 | | 8a-12=4(a-5) | | 6n^2+31n+18=0 | | 70m^2-73m+20= | | 2(x-8)=9 | | -2/3x=28 | | Q=j+jet | | X+78=x+41 | | -8=-2z+-14 | | 5y-6y+y+36=6y+30-2y | | 2u+6v=9 |